Seed sourcing strategies for ecological restoration under climate change: A review of the current literature - Vitt, Pati; Finch, Jessamine; Barak, Rebecca S.; Braum, Anna; Frischie, Stephanie; Redlinski, Izabella (Frontiers in Conservation Science, 2022)
Abstract (word count: 219) Climate change continues to alter the seasonal timing and extremes of temperature and precipitation patterns globally. These departures from historic conditions along with the predicted variability of future climates present a challenge to seed sourcing, or provenance strategy decisions within the practice of ecological restoration. The “local is best” assumption that ecotypes have genetic adaptation to their environment is potentially being outpaced by climate change and the limited ability of plant populations to naturally migrate or shift their distribution accordingly. Restoration practitioners and natural area managers have a general understanding of the importance of matching the inherent adaptations of source populations with the current and/or future site conditions where those seeds or propagules are planted. However, for many species used in seed-based restoration, there is a lack of empirical evidence to guide these seed sourcing decisions, which are critical for the longevity and ecological function of restored natural communities. With the goal of characterizing, synthesizing, and applying experimental research into guidance for restoration practice, we conducted a systematic review of the literature on seed sourcing strategies and climate resiliency. We describe the patterns and gaps our review identified, highlight specific topics which require further research, and provide practical suggestions of immediate and longer term tools that restoration practitioners can use to guide and build resilient natural communities under future climate scenarios.